PEMANFAATAN MEDIA PEMBELAJARAN DALAM MENINGKATKAN KUALITAS PEMBELAJARAN PAI DI SEKOLAH - Arfandi Arfandi (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2020)
In this globalization era, education technology programs, especially in Indonesia, have spread so quickly, not only in the level of basic education but also to the level of education at the college level. As an indication of the development of education technology, among others, there have been many different types of media learning in improving the quality of learning such as visual media, audio media, and audiovisual media. Of the various instructing media, all of which can support in the process of activities in learning and teaching, but the very urgent attention by every educator is that the use of the media not only look at the sophistication but more important is the quality of the implementation of learning activities in an educational institution, of course, it is necessary to adapt to some targets that are the mission of education. It is very important for a teacher in carrying out his duties as a teacher must have pedagogic competence, a teacher should have the ability to be in accordance with the methodology of learning both in terms of learning planning and in the implementation of learning. So, a teacher who already has competence and qualifications in both the mastery and ability in the use of learning media that will certainly affect the process of teaching actively, innovative, creative, and enjoyable.